DINAMIKA POPULASI DAN STATUS PEMANFAATAN TONGKOL ABU-ABU Thunnus tonggol DI PERAIRAN TELUK SEMANGKA - Yudha, Indra Gumay; Caesario, Rachmad; Rizki, Annas (Jurnal Teknologi Perikanan dan Kelautan, 2023)
Longtail tuna (Thunnus tonggol) is one of the economic fish that has been regulated in Indonesia and also caught in the waters of Semangka Bay, Lampung. In order to be managed properly, scientific data due to utilization are needed. The purpose of this study was to analyzed population dynamic and utilization of longtail tuna resources in the Bay Semangka waters, through assessment growth patterns, growth parameters, condition factors, utilization rates, and the spawning potential ratio (SPR). Data were based on distributions of Total Length (TL) from 515 samples of longtail tuna landed at Kota Agung Coastal Fishing Port during March-April 2022. Data were analyzed using FISAT II ver 1.2.2 and web.barefootecologist.com.au software. The results showed that longtail tuna had a negative allometric growth (b=2.2251), condition factor was approach value of 1.0, asymptotic length (L∞) of 813.33 mm, exploitation rate (E) of 0.84 year-1, and spawning potential ratio (LB-SPR) of 13%. These conditions showed that longtail tuna in the Semangka Bay had overfishing and the exploitation was feared to be unsustainable, therefore it needs to be managed properly.